OpenHVSR: imaging the subsurface 2D/3D elastic properties through multiple HVSR modeling and inversion - Bignardi, S.; Mantovani, A.; Abu Zeid, N. (Computers & geosciences, 2016)
OpenHVSR is a computer program developed in the Matlab environment, designed for the simultaneous modeling and inversion of large Horizontal-to-Vertical Spectral Ratio (HVSR or H/V) datasets in order to construct 2D/3D subsurface models (topography included). The program is designed to provide a high level of interactive experience to the user and still to be of intuitive use. It implements several effective and established tools already present in the code ModelHVSR by Herak (2008), and many novel features such as: -confidence evaluation on lateral heterogeneity -evaluation of frequency dependent single parameter impact on the misfit function -relaxation of Vp/Vs bounds to allow for water table inclusion -a new cost function formulation which include a slope dependent term for fast matching of peaks, which greatly enhances convergence in case of low quality HVSR curves inversion -capability for the user of editing the subsurface model at any time during the inversion and capability to test the changes before acceptance. In what follows, we shall present many features of the program and we shall show its capabilities on both simulated and real data. We aim to supply a powerful tool to the scientific and professional community capable of handling large sets of HSVR curves, to retrieve the most from their microtremor data within a reduced amount of time and allowing the experienced scientist the necessary flexibility to integrate into the model their own geological knowledge of the sites under investigation. This is especially desirable now that microtremor testing has become routinely used. After testing the code over different datasets, both simulated and real, we finally decided to make it available in an open source format. The program is available by contacting the authors. [Display omitted] •Capability of simultaneous handling of multiple HVSR curves (i.e. large datasets).•Modeling HVSR curves at multiple locations.•Inversion of multiple HVSR for 2D or 3D visco-elastic subsurface retrieval.•Original features, not previously seen in literature were introduced.•Allow the user the flexibility to intervene any time during the inversion process.